Reduced Interhemispheric Functional Connectivity in Obsessive–Compulsive Disorder Patients - Deng, Ke; Qi, Tianfu; Xu, Jian; Jiang, Linlin; Zhang, Fengrui; Dai, Nan; Cheng, Yuqi; Xu, Xiufeng (Frontiers in Psychiatry, 2019)
Background: The high synchrony of spontaneous neural activity in the homotopic region of the resting hemisphere is considered to be an important functional structural feature of normal human brain, while a series of studies of mental disorders such as depression, schizophrenia, dementia, and sleep disorders, the feature was found to be broken. Until now, the synchrony of spontaneous neural activity of the resting hemisphere in obsessive-compulsive disorder (OCD) remain unclear. Present study aimed to detect the abnormal synchrony of spontaneous neural activity in OCD. Methods: Forty-six patients with OCD and 46 -gender, -age and education matched healthy subjects (HC) received MRI scans. The voxel-mirrored homotopic connectivity (VMHC) method was used to evaluate the resting state functional connections between the both hemispheres of each subject. The two sample T-test was used to compare VMHC between OCD and HC. A partial correlation analysis was used to investigate the relationship between VMHC and clinical features in patients with OCD. Results: Compared to HC, the VMHC values were found decreased widely in many brain regions, such as bilateral fusiform gyrus/inferior occipital gyrus, bilateral lingual gyrus, bilateral postcentral gyrus/precentral gyrus, bilateral putamen and bilateral orbital frontal gyrus in patients with OCD. The values of VMHC in the bilateral angular gyrus/middle occipital gyrus were significantly correlated with illness duration. Conclusions: Interhemispheric functional coordination abnormalities may be one of the important pathophysiological mechanisms of OCD.